Preparation and Use of Cellular Reagents: A Low‐resource Molecular Biology Reagent Platform. Issue 3 (8th March 2022) - Bhadra, Sanchita; Paik, Inyup; Torres, Jose‐Angel; Fadanka, Stéphane; Gandini, Chiara; Akligoh, Harry; Molloy, Jenny; Ellington, Andrew D.
Abstract: Protein reagents are indispensable for most molecular and synthetic biology procedures. Most conventional protocols rely on highly purified protein reagents that require considerable expertise, time, and infrastructure to produce. In consequence, most proteins are acquired from commercial sources, reagent expense is often high, and accessibility may be hampered by shipping delays, customs barriers, geopolitical constraints, and the need for a constant cold chain. Such limitations to the widespread availability of protein reagents, in turn, limit the expansion and adoption of molecular biology methods in research, education, and technology development and application. Here, we describe protocols for producing a low‐resource and locally sustainable reagent delivery system, termed "cellular reagents, " in which bacteria engineered to overexpress proteins of interest are dried and can then be used directly as reagent packets in numerous molecular biology reactions, without the need for protein purification or a constant cold chain. As an example of their application, we describe the execution of polymerase chain reaction (PCR) and loop‐mediated isothermal amplification (LAMP) using cellular reagents, detailing how to replace pure protein reagents with optimal amounts of rehydrated cellular reagents. We additionally describe a do‐it‐yourself fluorescence visualization device for using these cellular reagents in common molecular biology applications. The methods presented in this article can be used for low‐cost, on‐site production of commonly used molecular biology reagents (including DNA and RNA polymerases, reverse transcriptases, and ligases) with minimal instrumentation and expertise, and without the need for protein purification. Consequently, these methods should generally make molecular biology reagents more affordable and accessible. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of cellular reagents Alternate Protocol 1 : Preparation of lyophilized cellular reagents Alternate Protocol 2 : Evaluation of bacterial culture growth via comparison to McFarland turbidity standards Support Protocol 1 : SDS‐PAGE for protein expression analysis of cellular reagents Basic Protocol 2 : Using Taq DNA polymerase cellular reagents for PCR Basic Protocol 3 : Using Br512 DNA polymerase cellular reagents for loop‐mediated isothermal amplification (LAMP) Support Protocol 2 : Building a fluorescence visualization device